The silent period in patients with chronic renal failure undergoing hemodialysis - Resende, Luiz Antonio de Lima [UNESP]; Caramori, Jacqueline Socorro Costa Teixeira [UNESP]; Kimaid, P. A. T.; Martin, Luis Cuadrado [UNESP]; Barretti, Pasqual [UNESP] (My University, 2002)
Silent period was evaluated in 20 adult male patients with chronic renal failure undergoing hemodialysis. Readings were obtained by supramaximal stimulus to the median nerve, during maximum isometric effort of the abductor pollicis brevis muscle against resistance. Two types of abnormalities were observed, motor neuron hypoexcitability with elongated silent period, and motor neuron hyperexcitability with reduction or absence of silent period. Some abnormalities are probably linked with dialysis duration, but show no correlation to presence or absence of peripheral neuropathy. The silent period alterations described in this study could possibly correlate with some other clinical feature frequently seen in patients with chronic renal failure such as hypereflexia of the deep tendon reflexes.
Keywords: adult; chronic kidney failure; electromyography; electrostimulation; female; hospitalization; human; male; middle aged; motoneuron; motor neuron disease; pathophysiology; peripheral neuropathy; physiology; reaction time; renal replacement therapy; skeletal muscle; time; clinical article; clinical feature; controlled study; correlation analysis; heart muscle; hemodialysis; hyperreflexia; hyporeflexia; latent period; median nerve; motor nerve conduction; motor neuropathy; muscle isometric contraction; nerve stimulation; sensory nerve conduction; tendon reflex; thumb; Adult; Electric Stimulation; Electromyography; Female; Humans; Kidney Failure, Chronic; Male; Middle Aged; Motor Neuron Disease; Motor Neurons; Muscle, Skeletal; Peripheral Nervous System Diseases; Reaction Time; Renal Dialysis; Severity of Illness Index; Time Factors; Human; Middle Age